Imaging Roles of Public Relations (PR) Texts in the Proprietary Media of the Corporate Brands - Hristova, Hristina (Media and Language, 2023)
The article considers the contribution of the proprietary media in the communication policy of business organizations. The aim of the study is to identify the general imaging functions of the different PR texts, published on the online platforms of the companies. The research is based on the hypothesis of the interaction between the individual contents and the dominant role of the PR texts in the narrative about the advantages of the corporate brands, competing for consumer’s attention in the digital communication environment. In order to achieve the research objective, the case study method was applied.